Analisis Mutu Produk Naget Substitusi Hati Ayam Kampung Unggul Balitbangtan (KUB) - Pradiptya Ayu Harsita; Hidayat Bambang Setyawan; Amam Amam (Bulletin of Applied Animal Research, 2022)
The product of naget which is substituted for chicken liver is an innovation in the development of livestock products that have added value and as a form of product diversification. This study aims to determine the quality of the product through the assessment of consumer acceptance of KUB chicken meat naget and KUB chicken liver substituted chicken nuggets. The research was conducted at the Laboratory of Animal Products Technology, Animal Husbandry Study Program, Faculty of Agriculture, University of Jember. The research was conducted with a quantitative descriptive approach. The variables observed were product quality testing which included color, texture, aroma, and taste attributes. Data were analyzed using Microsoft Excel 2010 for descriptive analysis and SPSS 25 program for statistical analysis. The results showed that the texture, aroma, and taste attributes of KUB chicken nuggets and KUB chicken liver substituted chicken nuggets had no difference, while the color attribute had a significant difference (P < 0.05). The conclusion of the study was that the color difference in the KUB chicken liver substitution nugget could reduce consumer acceptance, so the research recommendation was to add natural dyes, so that the substituted nugget had a bright color like KUB chicken nugget, so that the substituted nugget could be accepted by consumers.